Los medios didácticos en el proceso de enseñanza – aprendizaje de la lecto- escritura en los niños de primer año de Educación Básica de la Unidad Educativa Riobamba, cantón Riobamba. Año lectivo 2014 -2015 - Alvarado Estrella, Lilia Rocío (2016)
It is necessary to know that within the teaching-learning process, the aids are necessary contribution to an adequate development of reading - writing, In view of that this constitutes a problem inside the learning and improvement of the skills and capacities of children in the first Year of Basic Education of the Unidad Educativa Riobamba, Therefore it is necessary to perform a research adapted of this form to achieve that the acquired learning are the best. For the development of this research work the problem statement was made at macro, meso and micro level, general and specific objectives were raised , the research is justified by its impact, usefulness and beneficiarles of the research proposal took into account the background on issues related to the topic in the library of the Facultad de Ciencias de la Educación Humanas y Tecnologías , will be scientifícally substantiated and theoretically the two variables independent study and dependent where it was known , clear doubts and correctly apply concepts , definitions of terms , operationalization of variables where the indicators are the volume of the annual curriculum plan of the Ministerio de Educación and the teachers work with first-year of Basic Education developed, A methodological framework was applied , the type of research was field , descriptive , documentary and non-experimental , through observation, once the tab proceeded to tabúlate the information, then plotted where everyone has the analysis and interpretation and finally the conclusions and recommendations based on the results obtained was developed .Finally this type of work helps us to.